Nanotoxicology research at INSA – do NMs contribute for genotoxic effects that may lead to cancer? - Louro, Henriqueta (2020)
The technology based on manufactured nanomaterials (NMs) has been pointed as key enabling technology, due to its potential to improve many products and processes, namely in agriculture, food and feed industry. Many of such products, already available, have NMs, such as nano-encapsulates, silver, titanium dioxide nanomaterials (TiO2) or synthetic amorphous silica (SAS) and many others are being developed, such as nanocellulose and nanoformulations of pesticides. One major concern for public health is that NMs may produce adverse outcomes such as genotoxic effects that are associated with increased risk of cancer. Although NMs have been extensively investigated in recent years, the studies have generated contradictory results, possibly due to differences in the physicochemical properties of the NMs studied and to other variables in the tested systems. Furthermore, the NMs properties have been recognized as being context-dependent, i.e. can be affected by the surrounding matrix. These secondary features may be potentially more relevant for determining the toxicological outcome. In particular, processes like intake or digestion may modify the NMs characteristics leading to unexpected toxicity in human cells. Under the scope of two nationally funded projects (PTDC/SAU-PUB/29481/2017 – INGESTnano and PTDC/SAU-PUB/32587/2017- ToxApp4NanoCELFI), the research developed at INSA, focused on the nanogenotoxicology assessment of titanium dioxide nanomaterials and nanocelluloses will be presented.